Copper-Catalyzed Intramolecular C–H Amination: A New Entry to Substituted Xanthine Derivatives - Shimizu, Maki; Hayama, Noboru; Kimachi, Tetsutaro; Inamoto, Kiyofumi (Synthesis, 2017)
Catalytic synthesis of xanthines was achieved in the presence of a copper catalyst. The process involves copper-catalyzed intramolecular C–H amination of benzamidines that possess a uracil moiety and produces variously substituted xanthines generally in good to high yields. This work introduces a new, facile approach to polysubstituted xanthine compounds.
Keywords: copper; catalysis; C–H functionalization; amination; cyclization; xanthines